2018
DOI: 10.1590/2446-4740.01618
|View full text |Cite
|
Sign up to set email alerts
|

Real-time premature ventricular contractions detection based on Redundant Discrete Wavelet Transform

Abstract: Introduction: Premature Ventricular Contraction (PVC) is among the most common types of ventricular cardiac arrhythmia. However, it only poses danger if the person suffers from a heart disease, such as heart failure. Hence, this is an important factor to consider in heart disease people. This paper presents an ECG real-time analysis system for PVC detection. Methods: This system is based on threshold adaptive methods and Redundant Discrete Wavelet Transform (RDWT), with a real-time approach. This analysis is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Khalaf et al [37] proposed an SVM-based method on MATLAB R2010a on Intel ® Core™ i5 3.2 GHz processor and 8 GB RAM, and it consumed 54.8 ms for each beat classification. Arrais Junior et al [38] reported an adaptive threshold and redundant discrete wavelet transform fusion method, which can process 30 min signals using only 61.2 s on the Matlab 2014a platform. These results showed that (1) the superposition of deep learning and time-frequency conversion processes will increase the complexity of the algorithm; The employed DL-based method (LSTM-AE module) was used to extract features from ECG heartbeats for K-means clustering, and the PVC identification was based on a combination of multiple rules, including template matching and rhythm characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Khalaf et al [37] proposed an SVM-based method on MATLAB R2010a on Intel ® Core™ i5 3.2 GHz processor and 8 GB RAM, and it consumed 54.8 ms for each beat classification. Arrais Junior et al [38] reported an adaptive threshold and redundant discrete wavelet transform fusion method, which can process 30 min signals using only 61.2 s on the Matlab 2014a platform. These results showed that (1) the superposition of deep learning and time-frequency conversion processes will increase the complexity of the algorithm; The employed DL-based method (LSTM-AE module) was used to extract features from ECG heartbeats for K-means clustering, and the PVC identification was based on a combination of multiple rules, including template matching and rhythm characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the high-and low-frequency information of the signal or image is separated, and finally, it is decomposed into approximate signals and wavelet surfaces on different frequency channels. Moreover, the length of the approximation signal and the detail signal after the signal transformation are the same as the original signal length [39].…”
Section: Methods 221 Decomposition and Reconstruction Of Image Signal...mentioning
confidence: 99%
“…Junior et al developed a system based on threshold adaptive algorithm and wavelet transform for PVC detection. The result validated on the MIT-BIH arrhythmia database reported that Daubechies 2 wavelet mother is more indicated compared with Coiflets and Symlets [10]. Oliveira et al proposed a simplified set of features extracted from geometric figures constructed over QRS complexes and selected the most suitable classifiers based on the analytic hierarchy process (AHP).…”
Section: Introductionmentioning
confidence: 99%